2009
DOI: 10.4161/cc.8.23.10238
|View full text |Cite
|
Sign up to set email alerts
|

The reverse Warburg effect: Aerobic glycolysis in cancer associated fibroblasts and the tumor stroma

Abstract: Here, we propose a new model for understanding the Warburg effect in tumor metabolism. Our hypothesis is that epithelial cancer cells induce the Warburg effect (aerobic glycolysis) in neighboring stromal fibroblasts. These cancer-associated fibroblasts, then undergo myo-fibroblastic differentiation, and secrete lactate and pyruvate (energy metabolites resulting from aerobic glycolysis). Epithelial cancer cells could then take up these energy-rich metabolites and use them in the mitochondrial TCA cycle, thereby… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
1,099
2
19

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 1,171 publications
(1,155 citation statements)
references
References 55 publications
35
1,099
2
19
Order By: Relevance
“…38 Then, it was demonstrated that stromal cells may perform aerobic glycolysis under the influence of tumor cells and donate lactate to feed OxPhos metabolism of tumor cells, the so-called "Reverse Warburg Effect." [39][40][41] Metformin, a drug that is found to be effective in tumors, [42][43][44][45] when it was added in acidic medium, which will be used for MSC conditioning, blocks TGFb expression and reverts inhibition of GLUT 1 and 3 elicited by acidic medium in MSC. Moreover, melanoma cells conditioned by LpH-metformin-treated MSC medium exhibited a reconstituted epithelial-like profile and a reduced invasion, that were associated with a reduction of GLUT 1, 3.…”
Section: Discussionmentioning
confidence: 99%
“…38 Then, it was demonstrated that stromal cells may perform aerobic glycolysis under the influence of tumor cells and donate lactate to feed OxPhos metabolism of tumor cells, the so-called "Reverse Warburg Effect." [39][40][41] Metformin, a drug that is found to be effective in tumors, [42][43][44][45] when it was added in acidic medium, which will be used for MSC conditioning, blocks TGFb expression and reverts inhibition of GLUT 1 and 3 elicited by acidic medium in MSC. Moreover, melanoma cells conditioned by LpH-metformin-treated MSC medium exhibited a reconstituted epithelial-like profile and a reduced invasion, that were associated with a reduction of GLUT 1, 3.…”
Section: Discussionmentioning
confidence: 99%
“…This scenario seemingly resembles the so-called reverse Warburg effect, in which epithelial cancer cells were found to corrupt the stroma associated fibroblasts undergoing myo-fibroblastic differentiation to release micronutrients in the milieu, such as lactate and pyruvate, which are then taken up by cancer cells to produce energy in the mitochondria. 127 RMS cells might also exploit nutrients deriving from the fusion with other cells, since the fusion process has been observed occurring between ARMS cells and muscle satellite cells through a IL-4R-dependent mechanism. 128 In light of these important findings, the future lines of research should be devoted to a better understanding of the metabolism in RMS cells in both the undifferentiated and differentiated status.…”
Section: Targeting Intratumor Cell Heterogeneity: a Difficult But Promentioning
confidence: 99%
“…It in volves the coop tion of the meta bolic ac tiv i ties of stro mal cells by ox ida tive can cer cells in a process that can be viewed as meta bolic en slave ment or com men sal ism. Res pi ra tion is in deed as so ci ated with the pro duc tion of ROS, among which H O , which has a rel a tively long half life, can per me ate mem branes and can reach nearby fi brob lasts where it ox i dizes pro teins in clud ing those in volved in cel lu lar res pi ra tion [77]. When ex posed to paracrine H O , fi brob lasts un dergo ox ida tive dam age and switch from an ox ida tive to a more gly colytic me tab o lism, thus pro vid ing lac tate and ke tone bod ies to ox ida tive can cer cells that use these fu els to al i ment their own me tab o lism.…”
Section: Metabolic Cooperation In Cancermentioning
confidence: 99%